The Role of Internship Experience, Soft Skills, and Self-Efficacy in Enhancing Vocational Readiness: A Systematic Literature Review - Erika Marety Megasari; Yoto Yoto; Widiyanti Widiyanti (South Sulawesi Education Development (SSED), 2025)
This study presents a Systematic Literature Review (SLR) examining the combined influence of internship experiences, soft skills, and self-efficacy on vocational readiness in vocational education and training (TVET) contexts. Drawing upon 25 peer-reviewed articles published between 2019 and 2025, the review highlights the interconnected nature of these three factors in shaping students’ preparedness for the labor market. The findings reveal that internships play a crucial role in bridging the gap between school-based learning and industry requirements, equipping students with practical competencies and professional exposure. Soft skills, including communication, teamwork, problem-solving, and adaptability, are identified as essential for employability and workplace integration. Self-efficacy emerges as a psychological foundation that fosters motivation, resilience, and confidence, enabling students to succeed in both academic and professional settings. Importantly, the review underscores the synergistic relationship between these three dimensions, suggesting that integrative approaches are most effective in promoting holistic vocational readiness. Practical implications include the need for curriculum design that embeds structured internships, systematic soft skills training, and targeted interventions to enhance self-efficacy. The study also identifies limitations in research scope and proposes future studies that employ cross-cultural perspectives and longitudinal designs.